Lindtneria borinquensis (Stephanosporaceae, Agaricales), a new species from Puerto Rico - Miller, Kurt O.; Bernicchia, Annarosa; Gorjón, Sergio P. (Phytotaxa, 2025)
Lindtneria borinquensis sp. nov. is described from Puerto Rico, and characterized by a slightly tuberculate hymenophore, clamped generative hyphae, lack of cystidia and globose- subglobose basidiospores. Phylogenetically, the species presents an isolated position among other undescribed Lidntneria species and environmental samples.